Strategies of Traditional Retail Store in Dealing with Mini Market Competition in Sidoarjo Regency - Ibad, Moch Wasiul; Nugroho, Agung Dwi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the strategies adopted by traditional retail stores in Sidoarjo Regency to remain competitive amidst the rapid expansion of modern retail, particularly mini markets. Using a qualitative descriptive approach, data were collected through interviews, direct observations, and documentation involving five traditional store owners operating near mini market locations. The findings reveal that traditional retailers rely on several key strategies, including building strong social relationships with customers, offering flexible payment systems such as informal credit, adjusting product prices based on community purchasing power, and providing unique local products not found in mini markets. While these strategies help sustain competitiveness, challenges remain, especially regarding store management, layout, and limited use of digital technology. Therefore, collaborative support in managerial training, financial access, and technological empowerment is essential to enhance the competitiveness and sustainability of traditional retail businesses in the face of modern retail growth.